Human FOXP3+ T regulatory cell heterogeneity. Issue 1 (30th January 2018) - Mohr, Audrey; Malhotra, Rajneesh; Mayer, Gaell; Gorochov, Guy; Miyara, Makoto
Abstract: FOXP3‐expressing CD4 + T regulatory (Treg) cells are instrumental for the maintenance of self‐tolerance. They are also involved in the prevention of allergy, allograft rejection, foetal rejection during pregnancy and of exaggerated immune response towards commensal pathogens in mucosal tissues. They can also prevent immune responses against tumors and promote tumor progression. FOXP3‐expressing Treg cells are not a homogenous population. The different subsets of Treg cells can have different functions or roles in the maintenance of immune homeostasis and can therefore be differentially targeted in the management of autoimmune diseases or in cancer. We discuss here how Treg cell subsets can be differentiated phenotypically, functionally and developmentally in humans. Abstract : Human circulating and tissue infiltrating Treg cells are phenotypically heterogeneous. We discuss here how Treg subsets can be differentiated functionally in the maintenance of immune homeostasis and can be targeted as part of immunotherapy (autoimmune disease or cancer).